2020
DOI: 10.2196/19488
|View full text |Cite
|
Sign up to set email alerts
|

EatSmart, a Web-Based and Mobile Healthy Eating Intervention for Disadvantaged People With Type 2 Diabetes: Protocol for a Pilot Mixed Methods Intervention Study

Abstract: Background People of low socioeconomic position (SEP) are disproportionately affected by type 2 diabetes (T2D), partly due to unhealthy eating patterns that contribute to inadequate disease self-management and prognosis. Digital technologies have the potential to provide a suitable medium to facilitate diabetes education, support self-management, and address some of the barriers to healthy eating, such as lack of nutritional knowledge or shopping or cooking skills, in this target group. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Food can be both a powerful way to connect to people and a means to promote individual interest in self-care (Pettinger et al, 2017). Current programs seeking to decrease the negative health consequences caused by obesity or diabetes often strive to enhance cooking and food-related skills (Alpaugh et al, 2020; Karimi et al, 2020) but rely on self-report measures to capture changes in skill level. In addition, individuals with schizophrenia as well as the aging population have been identified as at risk for health problems due to food- and cooking-related challenges (Hamera & Brown, 2000; Plastow et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Food can be both a powerful way to connect to people and a means to promote individual interest in self-care (Pettinger et al, 2017). Current programs seeking to decrease the negative health consequences caused by obesity or diabetes often strive to enhance cooking and food-related skills (Alpaugh et al, 2020; Karimi et al, 2020) but rely on self-report measures to capture changes in skill level. In addition, individuals with schizophrenia as well as the aging population have been identified as at risk for health problems due to food- and cooking-related challenges (Hamera & Brown, 2000; Plastow et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…EatSmart, a 12-week, multimodality-delivered healthy eating intervention, included access to a website viewable on mobile devices or PCs and tailored SMS text messages designed for disadvantaged people with T2D. This intervention is described in detail in the protocol paper [ 21 ] and summarized in this section. The website consisted of 6 skill-based modules provided to participants on a 2-weekly basis and that covered various topics such as the importance of vegetable, fruit, and whole food intake for health and diabetes; smart shopping planning and food label reading; modification of recipes by trying and incorporating new types of vegetables; improvement of cooking skills and confidence; and a final reinforcement and summary module.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals who are pregnant or breastfeeding, those with visual or hearing impairment, and those who had an eating disorder with special medical or dietary requirements, clinical depression, planned surgery, or plans for long travel during the study period were not invited to the program. The inclusion and exclusion criteria have been fully described in the study protocol [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Feasibility trials typically involve 20-100 participants, and evaluate the suitability of outcome measures, participant acceptance of the intervention (recruitment and retention rates) and DHI usage (e.g. adherence) [28][29][30][31][32]. From our systematic review of five included studies, we found single cohort trials limited the strength of evidence of effectiveness as this methodology is inherently prone to confounding bias [33].…”
Section: Evaluating the Feasibility And Acceptability Of The Dhimentioning
confidence: 99%